2020
DOI: 10.3390/nu12020576
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Dietary Agmatine Sulfate Effectiveness in Neuropathies Associated with Painful Small Fiber Neuropathy. A Pilot Open-Label Consecutive Case Series Study

Abstract: Peripheral neuropathies associated with painful small fiber neuropathy (SFN) are complex conditions, resistant to treatment with conventional medications. Previous clinical studies strongly support the use of dietary agmatine as a safe and effective treatment for neuropathic pain. Based on this evidence, we conducted an open-label consecutive case series study to evaluate the effectiveness of agmatine in neuropathies associated with painful SFN (Study Registry: ClinicalTrials.gov, System Identifier: NCT0152466… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Of note, NOS pathway has been shown to be upregulated by both Ang (1-7)/MasR and Ang (1-9)/AT2 receptor pathways that are downstream ACE2 activity [38,39,41,43]. Moreover, agmatine has a regulated plasma concentration in the range of 20-80 ng/mL and the use of dietary agmatine has been shown to be safe and effective in reducing neuropathic pain [129]. Moreover, agmatine sulfate is regularly taken as a bodybuilding supplement.…”
Section: Safety and Efficacy Concerns Of Chelating Agentsmentioning
confidence: 99%
“…Of note, NOS pathway has been shown to be upregulated by both Ang (1-7)/MasR and Ang (1-9)/AT2 receptor pathways that are downstream ACE2 activity [38,39,41,43]. Moreover, agmatine has a regulated plasma concentration in the range of 20-80 ng/mL and the use of dietary agmatine has been shown to be safe and effective in reducing neuropathic pain [129]. Moreover, agmatine sulfate is regularly taken as a bodybuilding supplement.…”
Section: Safety and Efficacy Concerns Of Chelating Agentsmentioning
confidence: 99%
“…Scientific studies indicate the synergism of agmatine with analgesic drugs from the opioid group in terms of analgesic activity. Agmatine reduces the addictive potential of opioids and limits the development of tolerance [204,205,206] …”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 99%
“…Few clinical trials have been performed on the use of agmatine. In a clinical trial in patients with neuropathic pain, agmatine was shown to have analgesic activity [205] . In a study on patients with depression, the application of agmatine at the dose of 2–3 g per day led to remission of depression symptoms.…”
Section: Ingredients Permitted (Or Not Specified) By Wadamentioning
confidence: 99%
“…Indeed, NAAE is a weak ACE2 inhibitor, it is in fact more than a thousand-fold less potent than MLN-4760; however, if agmatine will be proven to have ACE2 inhibitory activity, it might be helpful to prevent the trigger of the positive feedback loops in the first mild phases of the disease. To this regard, the use of dietary agmatine has been shown to be safe and effective in reducing neuropathic pain [76] and agmatine sulfate is regularly taken as a bodybuilding supplement.…”
Section: Spike-ace2 Complexes Are Still Sensitive To Ace2 Inhibitors:mentioning
confidence: 99%